2011
DOI: 10.1016/j.reprotox.2010.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Developmental dioxin exposure of either parent is associated with an increased risk of preterm birth in adult mice

Abstract: We have previously described diminished uterine progesterone response and increased uterine sensitivity to inflammation in adult female mice with a history of developmental exposure to TCDD (2,3,7,8-tetrachlorodibenzo-p-dioxin). Since parturition in mammals is an inflammatory process mediated in part by a decline in progesterone action, toxicant-mediated disruption of progesterone receptor (PR) expression at the maternal-fetal interface would likely impact the timing of birth. Therefore, in the current study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 59 publications
(83 reference statements)
3
63
0
Order By: Relevance
“…Early life microbial exposures facilitate the maturation of dendritic cells (DCs) (Hoeman, Dhakal, and Zaghouani 2010; Troy and Kasper 2010) and expand the repertoire of immune functions to include Th1, Th17, and other immune response patterns. Prenatal and/or early postnatal exposure to toxicants (e.g., alcohol, heavy metals, tobacco smoke), certain infectious agents (e.g., gram-negative bacteria), and dietary factors (e.g., prenatal overnutrition, postnatal formula feeding) can alter the normal trajectory of innate immune maturation contributing to tissue pathology rather than adequate host resistance and tissue homeostasis (Auten et al 2009; Beloosesky et al 2010; Bry, Hogmalm, and Backstrom 2010; Caicedo et al 2008; Calderon-Garciduenas et al 2009; Ding et al 2010; Fry et al 2007; Sharkey et al 2009; Tomat, Costa Mde, and Arranz 2011). These alterations in immune function have the potential to change the trajectory of subsequent pathogen-stimulated innate immune responses throughout life (Perrone et al 2010; Strunk et al 2011).…”
Section: Innate Immunity and The Developing Immune Systemmentioning
confidence: 99%
“…Early life microbial exposures facilitate the maturation of dendritic cells (DCs) (Hoeman, Dhakal, and Zaghouani 2010; Troy and Kasper 2010) and expand the repertoire of immune functions to include Th1, Th17, and other immune response patterns. Prenatal and/or early postnatal exposure to toxicants (e.g., alcohol, heavy metals, tobacco smoke), certain infectious agents (e.g., gram-negative bacteria), and dietary factors (e.g., prenatal overnutrition, postnatal formula feeding) can alter the normal trajectory of innate immune maturation contributing to tissue pathology rather than adequate host resistance and tissue homeostasis (Auten et al 2009; Beloosesky et al 2010; Bry, Hogmalm, and Backstrom 2010; Caicedo et al 2008; Calderon-Garciduenas et al 2009; Ding et al 2010; Fry et al 2007; Sharkey et al 2009; Tomat, Costa Mde, and Arranz 2011). These alterations in immune function have the potential to change the trajectory of subsequent pathogen-stimulated innate immune responses throughout life (Perrone et al 2010; Strunk et al 2011).…”
Section: Innate Immunity and The Developing Immune Systemmentioning
confidence: 99%
“…In agreement with data from other groups (reviewed by [19]), we found that developmental toxicant exposure of male mice (F1) negatively impacted adult fertility. However, it was somewhat unexpected that mating fertile F1 males to control female mice resulted in a similar rate of PTB as observed with toxicant exposed females mated to control males [20]. Significantly, multiple studies have demonstrated that paternally expressed genes predominate within the placenta [21][23].…”
Section: Introductionmentioning
confidence: 95%
“…Specifically, as shown in Table 1 within each litter, some male and female mice exhibit infertility at sexual maturity while other animals exhibit normal fertility when mated to an unexposed partner. Among mating pairs of mice achieving pregnancy, a relatively high rate of spontaneous PTB was also observed [4, 29]. Again, reflecting our in vitro findings following acute exposure of human endometrial cells and tissues to TCDD, the occurrence of PTB in toxicant exposed F1 female mice occurred coincident with the phenotype of reduced uterine progesterone responsiveness and heightened sensitivity to inflammatory signals during pregnancy [4, 29].…”
Section: Evidence For Early Life Origins Of Reproductive Dysfunction mentioning
confidence: 53%
“…Since progesterone plays an absolutely critical role in stabilizing the maternal-fetal interface in support of pregnancy, we focused our rodent work on the ability of TCDD to disrupt the anti-inflammatory action of progesterone during gestation. As discussed below, we have linked developmental toxicant exposure of female mice to reduced fertility and an elevated risk of PTB for multiple generations [4] while a similar toxicant exposure of male mice also leads to adverse reproductive outcomes [2930]. Given the findings of our rodent model and others as noted above, it would be prudent to consider the possibility that early life environmental exposures in women might lead to epigenetic modifications that negatively affect adult reproductive tract function.…”
Section: Environmental Endocrine Disruptors In Reproductionmentioning
confidence: 99%